2001
DOI: 10.1002/icd.248
|View full text |Cite
|
Sign up to set email alerts
|

Mother's face recognition in newborn infants: learning and memory

Abstract: Two studies are reported that address issues related to memory for faces in young infants. The first correlates the opportunity to view the mother's face with expressed visual preference for that face, and shows that very little exposure is required, with greater levels of exposure showing stronger preferences. The second study examines the role of delay between exposure to the mother's face and preference testing, finding that strength of preference is not significantly impacted by a 15-min delay. Implication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
156
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(162 citation statements)
references
References 18 publications
(32 reference statements)
5
156
1
Order By: Relevance
“…the mother) appears most often, the FSA response to that face becomes stronger than to a similar stranger (Figure 7;Bednar and Miikkulainen (2002)). This result replicates the mother preference found in infants a few days old (Bushnell 2001;Pascalis et al 1995). Interestingly, the model no longer prefers the mother when her hair outline is masked, which is consistent with Pascalis et al's claim that newborns learn outlines only.…”
Section: Face Preference Experimentssupporting
confidence: 89%
See 3 more Smart Citations
“…the mother) appears most often, the FSA response to that face becomes stronger than to a similar stranger (Figure 7;Bednar and Miikkulainen (2002)). This result replicates the mother preference found in infants a few days old (Bushnell 2001;Pascalis et al 1995). Interestingly, the model no longer prefers the mother when her hair outline is masked, which is consistent with Pascalis et al's claim that newborns learn outlines only.…”
Section: Face Preference Experimentssupporting
confidence: 89%
“…A number of studies have found that newborns prefer facelike patterns (Goren, Sarty, and Wu 1975;Johnson, Dziurawiec, Ellis, and Morton 1991;Simion, Valenza, and Umiltà 1998), and others show that newborns can discriminate between specific faces and learn to prefer a particular face within the first few hours and days after birth (Bushnell 2001;Pascalis, de Schonen, Morton, Deruelle, and Fabre-Grenet 1995). When shown moving schematic faces in the visual periphery, newborns and one-month-olds will follow them further than other similar patterns (Goren et al 1975;; see example schematics in Figure 6b-e).…”
Section: Development Of Face Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, infants possess an innate face interest mechanism which facilitates early attention to faces (Morton & Johnson, 1991) and drives an early preference for looking at their mother's face over a stranger's face (e.g., Bushnell, 2001;Field, Cohen, Garcia & Greenberg, 1984;Pascalis, de Schonen, Morton, Deruelle, & Fabre-Grenet, 1995). This preference, which is present within the first days of life, enables the formation of the mother-infant relationship which is important for infant's social and emotional development (Bowlby, 1969;Blass & Camp, 2003).…”
Section: Introductionmentioning
confidence: 99%